2015
DOI: 10.1177/2158244015590163
|View full text |Cite
|
Sign up to set email alerts
|

Rising to the Challenge

Abstract: Writing is recognized as a vital skill in education and the workplace; students in the United States finishing K-12 schooling are expected to be competent writers. Yet, the Nation’s Report Card found that U.S. high school graduates coming into the workforce are particularly deficient in writing skills. Teachers serve as a crucial link in the move to improve literacy skills of K-12 students; however, teachers themselves are underprepared to be writers and writing teachers. Therefore, there is an urgent need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…As the participants are pre-service teachers, making them familiar with the process approach can prepare them for a future career as English teachers. One of the pedagogical implications of process-based writing is based on the findings of a study conducted by Li and Zhang (2015), which indicated that the teachers who participate in process-based writing had understood the principle of process-based writing, have learned the stages of process-based writing starting from planning, drafting, revising, editing, and sharing, and have high confidence to be writing teachers as well as writers. It is also in line with Street and Stang's (2008) findings that the majority of teachers(79%) who have joined process-based writing course become more confident to do their duties as teachers in giving the materials, checking students' works, giving feedback and evaluation.…”
Section: Table2 the Significant Difference In The Level Of Anxietymentioning
confidence: 99%
“…As the participants are pre-service teachers, making them familiar with the process approach can prepare them for a future career as English teachers. One of the pedagogical implications of process-based writing is based on the findings of a study conducted by Li and Zhang (2015), which indicated that the teachers who participate in process-based writing had understood the principle of process-based writing, have learned the stages of process-based writing starting from planning, drafting, revising, editing, and sharing, and have high confidence to be writing teachers as well as writers. It is also in line with Street and Stang's (2008) findings that the majority of teachers(79%) who have joined process-based writing course become more confident to do their duties as teachers in giving the materials, checking students' works, giving feedback and evaluation.…”
Section: Table2 the Significant Difference In The Level Of Anxietymentioning
confidence: 99%